A structural model of the relationships between optimism and perceived emotional intelligence on bullying victimization and health. - Serrano-Ibáñez, Elena Rocío; López-Martínez, Alicia Eva; Ruiz-Párraga, Gema Teresa; Esteve-Zarazaga, Rosa; Ramírez-Maestre, María del Carmen; Rey-Peña, Lourdes (My University, 2015)
Bullying is a relationship in which an individual, or a group of individuals, intentionally and repeatedly perpetrates aggressive behaviors towards someone unable to defend himself/herself. Traditional forms of bullying consist of physical, verbal and covert forms of aggressive behaviors. Recently, the new phenomenon of cyberbullying has emerged. This relatively new form of bullying is defined as a behavior displayed through electronic or digital media. Multiple variables have been related to bullying victimization including perceived emotional intelligence (PEI) and optimism. Both variables have implications on the manner in which people cope with stressful experiences as could be bullying, which in turn could affect the level of perceived health. However, there are no studies that have considered all these variables simultaneously. Therefore, the aim of the current study was to examine, via structural equation modelling, the independent contribution of EI and optimism on bullying victimization and perceived physical health in adolescents. A total of 650 secondary school students (317 boys and 333 girls, with ages ranged from 11 to 18) participated in the study. The participants completed measures of PIE (TMMS-24; Fernández-Berrocal et al., 2004), optimism (General Mood Subscale of the Emotional Quotient Inventory-Youth Version; Bar-On and Parker, 2000), bullying (School Victimization Scale; Cava et al., 2010), cyberbullying (Cyber-Victimization Scale; Buelga et al., 2012), and physical health (KIDSCREEN-10 Index; Raven-Sieberer et al., 2004). Results gave partial empirical support to the hypothesized model, and shows significant relationships between the variables: optimism on clarity and repair dimensions of IE (but not on the attention subscale), optimism and attention (but not clarity and repair dimensions) on bullying, and bullying on health. Together these findings shed light on those factors that should be considered when developing prophylactic strategies within adolescents to become more resilient to the adverse effects of bullying behavior.
Keywords: Inteligencia emocional; Optimismo; Adolescentes; Bullying; Optimism; Emotional intelligence; Health; Adolescents